2012
DOI: 10.1371/journal.ppat.1002563
|View full text |Cite
|
Sign up to set email alerts
|

Identification of O-mannosylated Virulence Factors in Ustilago maydis

Abstract: The O-mannosyltransferase Pmt4 has emerged as crucial for fungal virulence in the animal pathogens Candida albicans or Cryptococcus neoformans as well as in the phytopathogenic fungus Ustilago maydis. Pmt4 O-mannosylates specific target proteins at the Endoplasmic Reticulum. Therefore a deficient O-mannosylation of these target proteins must be responsible for the loss of pathogenicity in pmt4 mutants. Taking advantage of the characteristics described for Pmt4 substrates in Saccharomyces cerevisiae, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…Recent studies on the human pathogenic yeast C. albicans and the plant pathogenic fungus Ustilago maydis also demonstrated that O-mannosylation is required for adherence, invasion of host tissues, and virulence (45,46). A previous study on the function of the PMT family proteins in C. neoformans reported that pmt1⌬ and pmt4⌬ mutants displayed defects in cell morphology and severely attenuated virulence in a murine inhalation model of cryptococcosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the human pathogenic yeast C. albicans and the plant pathogenic fungus Ustilago maydis also demonstrated that O-mannosylation is required for adherence, invasion of host tissues, and virulence (45,46). A previous study on the function of the PMT family proteins in C. neoformans reported that pmt1⌬ and pmt4⌬ mutants displayed defects in cell morphology and severely attenuated virulence in a murine inhalation model of cryptococcosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…An example of each comes again from U. maydis. Pmt4 encodes an o-mannosyl transferase, modifying proteins as they leave the endoplasmic reticulum; its targets include a mucin involved in appressorium formation encoded by the Msb2 gene, and the Pit1 gene, whose product is involved in later stages of virulence, allowing the fungus to spread throughout the leaf [40]. Pit1 is genetically linked to a secreted putative effector encoded by Pit2; the Pit2 protein is membrane bound at fungal tips, and the authors hypothesize that Pit2 shuttles defense signals to Pit1, helping disguise the fungus from being detected [41].…”
Section: Future Challenges and New Directions In Effector Biologymentioning
confidence: 99%
“…In plants, most of the localization studies of T3Es have been performed in Agrobacterium tumefaciens-mediated transient expression systems using constitutive promoters (Block and Alfano, 2011;Macho, 2016). However, several biochemical studies revealed bacterial effectors undergo posttranslocational modification for proper targeting in the host cells (Boucrot et al, 2003;Reinicke et al, 2005;Patel et al, 2009;Fernández-Álvarez et al, 2012). Therefore, Agrobacterium-mediated expressions may not reflect dynamic localization of respective effectors originally secreted by T3SS.…”
Section: Introductionmentioning
confidence: 99%